Process-based modelling of the impacts of land use change on the water balance in the Cerrado Biome (Rio das Mortes, Brazil) - Meister, Sarina; Nobrega, Rodolfo L. B.; Rieger, Wolfgang; Wolf, Ronja; Gerold, Gerhard (ERDKUNDE, 2017)
Since the 1980s, the state of Mato Grosso, Brazil, exhibits high rates of Cerrado conversion in favour of soybean expansion and cattle ranching. This conversion process becomes obvious in the upper Rio das Mortes macro-catchment. The objective of this study was to assess the influence of future land use changes on the discharge dynamics of the Rio das Mortes River. A single catchment approach was applied with the physically-based water balance simulation model WaSiM 8.5.0 (Schulla and Jasper 2007) to simulate land use scenarios. In Scenario 1, only small pasture sites (< 1 km²) were converted into the respective land use type surrounding them (i.e. cropland or Cerrado vegetation), whereas in Scenario 2 all pasture sites were converted into cropland and all Cerrado patches were then transformed into pastures. The WaSiM model was calibrated and validated based on discharge data measured at two gauging stations, achieving Nash-Sutcliffe coefficients of 0.81 (calibration) and 0.68 (validation). Main problems in modelling arise because of scarce spatial distributed data on subsurface parameter and vegetation parameter (Cerrado biome). Therefore, the use of the numerical groundwater model and manifold calibration runs were essential in this modelling approach to allow the simulation of the high levels of baseflow during the dry season and the transition from the dry to the wet season. The immediate rise of the baseflow in response to the increasing precipitation at beginning of the rainy season is a result of high soil hydraulic conductivity and groundwater recharge. These soil characteristics apparently persist on newly-created pasture and cropland sites, which still exhibit high ksat values after deforestation. Simulated evapotranspiration is comparable to literature values (Eddy flux measurements, MODIS-EVI calculation) and recently done paired micro-catchment studies in this catchment. The scenario analysis indicates that there are only small differences in runoff volume, which is directly related to the precipitation changes. In the scenario 2, groundwater recharge and base flow increase, whereas surface runoff does not. Therefore, the ongoing land use intensification with pasture conversion to cropland, remaining high infiltration and slight increase of evapotranspiration may not change runoff volume and discharge characteristics.